MFGE8 does not influence chorio-retinal homeostasis or choroidal neovascularization in vivo. - William Raoul; Lucie Poupel; David-Alexandre Tregouet; Sophie Lavalette; Serge Camelo; Nicole Keller; Sophie Krumeich; Bertrand Calippe; Xavier Guillonneau; Francine Behar-Cohen; Salomon-Yves Cohen; Holger Baatz; et al. (PLoS ONE)
Purpose Milk fat globule-epidermal growth factor-factor VIII (MFGE8) is necessary for diurnal outer segment phagocytosis and promotes VEGF-dependent neovascularization. The prevalence of two single nucleotide polymorphisms (SNP) in MFGE8 was studied in two exsudative or "wet" Age-related Macular Degeneration (AMD) groups and two corresponding control groups. We studied the effect of MFGE8 deficiency on retinal homeostasis with age and on choroidal neovascularization (CNV) in mice. Methods The distribution of the SNP (rs4945 and rs1878326) of MFGE8 was analyzed in two groups of patients with "wet" AMD and their age-matched controls from Germany and France. MFGE8-expressing cells were identified in Mfge8(+/-) mice expressing ß-galactosidase. Aged Mfge8(+/-) and Mfge8(-/-) mice were studied by funduscopy, histology, electron microscopy, scanning electron microscopy of vascular corrosion casts of the choroid, and after laser-induced CNV. Results rs1878326 was associated with AMD in the French and German group. The Mfge8 promoter is highly active in photoreceptors but not in retinal pigment epithelium cells. Mfge8(-/-) mice did not differ from controls in terms of fundus appearance, photoreceptor cell layers, choroidal architecture or laser-induced CNV. In contrast, the Bruch's membrane (BM) was slightly but significantly thicker in Mfge8(-/-) mice as compared to controls. Conclusions Despite a reproducible minor increase of rs1878326 in AMD patients and a very modest increase in BM in Mfge8(-/-) mice, our data suggests that MFGE8 dysfunction does not play a critical role in the pathogenesis of AMD.